Tomato Powder Modulates NF-?B, mTOR, and Nrf2 Pathways during Aging in Healthy Rats - Şahin, Kazım; Orhan, Cemal; Tuzcu, Mehmet; Tastan, Hakki; Bilir, Birdal; Şahin, Nurhan; Küçük, Ömer (Hindawi Ltd, 2019)
Purpose. In the present study, we aimed to investigate the effects of tomato powder (TP) on glucose and lipid metabolism, as well as oxidative stress and the NF-kappa B, mTOR, and Nrf2 pathways during the aging process in healthy rats. Methods and Results. Male Wistar rats were randomly assigned to four groups as follows: (i) Control group 1 (n = 15, 3-week old): rats were fed standard diet for 7 weeks; (ii) TP group 1 (n = 15, 3-week old): rats were fed standard diet supplemented with TP for 7 weeks; (iii) Control group 2 (n = 15, 8-week old): rats were fed standard diet for 69 weeks; and (iv) TP group 2 (8-week old): rats were fed standard diet supplemented with TP for 69 weeks. TP supplementation significantly reduced the hyperglycemia, hypertriglyceridemia, and hypercholesterolemia and improved liver function and kidney function in 77-week old rats compared with the control animals (P < 0.05). In addition, TP significantly decreased the serum and liver MDA levels (P < 0.003 and P < 0.001, respectively) while increasing the activities of liver SOD (P < 0.001), CAT (P < 0.008), and GPx (P < 0.01) compared with the control groups in both 10-week-old and 77-week-old rats (P < 0.05). Age-related increases in phosphorylation of NF-kappa Bp65, mTOR, 4E-BP1, and P70S6K were observed in livers of 77-week-old rats compared to those of 10-week-old rats (P < 0.001). TP supplementation decreased the expression of NF-kappa Bp65 and activation of mTOR, 4E-BP1, and P70S6K in livers of 77-week-old rats compared to the control animals. Moreover, TP supplementation significantly elevated Nrf2 expression in livers of both 10-week-old and 77-week-old rats (P < 0.05). Conclusion. TP ameliorates age-associated inflammation and oxidative stress through the inhibition of NF kappa Bp65, mTOR pathways, and Nrf2 activation may explain the observed improvement in glucose and lipid metabolism as well as the improved liver and kidney functions.
Keywords: Oxidative Stress; Lycopene; Antioxidant; Mechanisms; Expression; Supplementation; Cancer; Phytochemicals; Inflammation; Resveratrol